Leaf micromorphological adaptation of Pogostemon spp. (section Eusteralis) in Thailand - Pramali, Kanjana; Bongcheewin, Bhanubong; Traiperm, Paweena (Agriculture and Natural Resources, 2018)
Pogostemon section Eusteralis is comprised of diverse taxa found in a range of habitats, from terrestrial to aquatic/marshland. However, few studies have examined the leaf micromorphology of Pogostemon and the micromorphological adaptations of this section to their habitats. Therefore, leaf micromorphological characters of the section Eusteralis in Thailand were investigated to assess the relationships between leaf micromorphological characters and environmental conditions and to explore alternative taxonomic characters for supporting the infrageneric classification. Common leaf micromorphological characters of this section were striate cuticular ornamentation, capitate trichomes with two apical cells, peltate trichomes with a large head cell, a convex outline of the abaxial side of the midrib and crescent collateral vascular bundles with a parenchymatous sheath. Variable leaf micromorphological characters were observed and appeared to be associated with environmental habitat conditions. The correlation between leaf micromorphology and environmental factors were considered and it was suggested that the major factor causing different leaf micromorphology is water availability. The important leaf micromorphological trait of Eusteralis that can distinguish this section from the section Pogostemon is the type of nonglandular trichomes; the section Eusteralis possesses only simple unicellular and bicellular trichomes, but no simple multicellular trichomes were found in the section Eusteralis, unlike in the section Pogostemon. This might be used as an additional character to define the infrageneric classification of Pogostemon.